Utilizing body percussion in the elementary music classroom - Downey, Stephanie (Kansas State University, 2023)
For my project, I created a series of lessons to facilitate student learning in elementary music based on the principles of the Orff approach and the Music Learning Theory. These lessons formed a unit covering half notes in Western music notation and included both familiar and unfamiliar methods of instruction during my teaching. First, students echoed various body percussion patterns to expose them to the half note rhythm contextually within four beats. Afterwards, they echoed body percussion of an unknown song to become familiar with the rhythm prior to hearing the melody played on the piano, followed by adding the lyrics. Next, students were taught the rhythm syllables, and practiced using them through aural training to identify both spoken and played half notes. Finally, students were introduced to the Western notation and began reading familiar patterns and songs, as well as unfamiliar classical music. Students finished the unit by creating body percussion compositions to accompany a song on their upcoming concert. Teaching a song and rhythms using body percussion was new to me, and I was surprised at how quickly the students were able to transition to ear training as well as notation reading after including it in the preparation and exposure stage of the unit. During my time in Kansas State University’s Master of Music program, I gained clarity in my teaching philosophy, which specifically benefited my upper elementary and middle school general music classrooms. Prior to beginning this program, I struggled with knowing what to teach in the middle school classroom when the students were not preparing for a performance. As I completed various assignments and courses, it became clear that a design shift in the structure of the specific class was beneficial, and I used my knowledge gained through the program to create a new scope and sequence for the class. Students in my middle school music class now explore popular music through ukulele instruction, participate in a cover band project, and complete a wide variety of projects that inspire their creativity and connectedness to music. Changing up this class structure encouraged me to shift my mindset, trust my philosophy, and experiment with new methodologies and lessons even in my elementary music classroom.
Keywords: Elementary music education; Body percussion; Elementary music composition